Synthesis and biological evaluation of novel N3-substituted dihydropyrimidine derivatives as T-type calcium channel blockers and their efficacy as analgesics in mouse models of inflammatory pain. Issue 6 (15th March 2017) - Teleb, Mohamed; Zhang, Fang-Xiong; Huang, Junting; Gadotti, Vinicius M.; Farghaly, Ahmed M.; AboulWafa, Omaima M.; Zamponi, Gerald W.; Fahmy, Hesham
Graphical abstract: Highlights: Novel N 3-substituted dihydropyrimidine derivatives as selective T-type calcium channel blockers. Evaluation of L-/T-calcium channel antagonism by whole patch clamp technique. Novel N 3-substituted dihydropyrimidines reduce the formalin-induced nocifensive response. Novel N 3-substituted dihydropyrimidines reduce the CFA-induced mechanical hyperalgesia. Abstract: Low-voltage-activated calcium channels are important regulators of neurotransmission and membrane ion conductance. A plethora of intracellular events rely on their modulation. Accordingly, they are implicated in many disorders including epilepsy, Parkinson's disease, pain and other neurological diseases. Among different subfamilies, T-type calcium channels, and in particular the CaV 3.2 isoform, were shown to be involved in nociceptive neurotransmission. The role of CaV 3.2 in pain modulation was supported by demonstrating selective antisense oligonucleotide-mediated CaV 3.2 knockdown, in vivo antinociceptive effects of T-type blockers, and pain attenuation in CaV 3.2 knockout formalin-induced pain model. These Emerging investigations have provided new insights into targeting T-type calcium channels for pain management. Within this scope, various T-type calcium channel blockers have been developed such as mibefradil and ethosuximide. Although being active, most of these molecules interact with other receptors as well. This addresses the need for T-selectivity. Few selective T-type channel blockers of diverse chemical classes were developed such as ABT-639 and TTA-P2. Interestingly, R (-) efonidipine which is a dihydropyridine (DHP) showed T-channel selectivity. Systematic modification of 1, 4-dihydropyridine scaffold introduced novel derivatives with 40-fold T-type selectivity over L-type calcium channels. Along these lines, substitution of the DHP core with various analogues favored T-selectivity and may serve as novel pharmacophores. Several dihydropyrimidine (DHPM) mimics were introduced by Squibb as potential candidates. As a continuation of this approach, the current study describes the synthesis of Novel N3 substituted DHPMs with structure similarities to the active DHPs. Different functional groups were introduced to the N3 position through a spacer to gain more information about activity and selectivity. Furthermore, the spacer aims at improving the metabolic stability of the molecules. Initial screening data by whole patch clamp technique showed a robust inhibition of Cav 3.2 T-type channels by eleven compounds. Interestingly, four compounds of these were efficient selective T-type blockers. Based on selectivity and efficiency, two compounds were selected for in vivo evaluation in mouse models of inflammatory pain. Results showed effective attenuation of nociception and mechanical hypersensitivity.